The Impact of Administrative Punishment on Business Dishonest Practices - Zedani, Fadila (Journal of Legal Studies and Researches, 2026)
The idea of administrative sanction as a system and a right granted to management under various texts through which it intervenes whenever the public interest calls for it, especially in the field of rules applied to commercial practices in order to achieve market protection from various practices that affect integrity, as well as imposing penalties on the violations committed. Therefore, the administrative penalty has a deterrent nature as a mechanism to deter the violations committed that affect the integrity of commercial practices, it is a guarantee of the addressees' commitment to respecting the laws and regulations imposed in the market.